Hubungan Antara Asupan Energi Dan Protein Dari Sarapan Pagi Dengan Prestasi Belajar Siswa Di SD Negeri Sumber III Surakarta - Pustika, Merlyana; , Endang Nur W, S.St., M.Si.Med; , Pramudya Kurnia, STP, M.Agr (2015)
Introduction : Student is the most importand investmen in nation because they will be the next generation of nation. The lack of protein and energy can reduce the anti body and concentration of student. Breakfast gives the most important role in supplying the energy. Student who does not have breakfast can experience the reduction of glucose, so that the brain would lacks Energy. This situation makes the body trembling, tired and also less concentration in study. Purpose :The research purpose are to describe the protein intake and energy from breakfast and to analyze the relationship between protein and energy intake from breakfast and the achievement of students. Research Methods :This research belongs to descriptive observational research. The samples of this research are students in the fourth, fifth and sixth grade at SD Negeri Sumber III, district of Banjarsari, Surakarta. There are 68 samples of student. The technique in taking research sample is using simple random sampling. The data of protein and energy from breakfast are using recall method of breakfast. The identity of respondent is using direct interview with are respondents. Results :The results of this research show that there are 63% students lack of energy, 49% students lack of protein and most students have a good achievement 66%. Conclusion :The result of the relation between breakfast energy and the students achievement of the study is p = 0,030 while the result of the relation between protein from breakfast and the students achievement p = 0,046. Suggestion : The direction of school should coordinate with the students parents for giving the knowledge of the importance of having breakfast which can build up the concentration and achievement of study.